Exploring the Prospective Biology Teachers’ Field-Trip Experiences as an Outdoor Learning Activity - Çetin, Gülcan (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
The study aimed to identify the views of prospective biology students on the field-trip experience as an outdoor learning activity in both educational and social contexts. It employed a qualitative phenomenological analysis method. Participants included 38 prospective biology teachers in an education faculty in the Marmara region in Türkiye. The field trip was held at İzmir Bird Paradise, Natural History Museum and Botanical Garden in İzmir, Türkiye. Data was collected by an open-ended question form before and after the field trip. Content analysis techniques were used to analyze the data. The results of this examination showed that the students were mainly content with the social activities, courses, İzmir Bird Paradise, the Natural History Museum, and the Botanical Garden, respectively, after the field trip.